2018
DOI: 10.1186/s13705-018-0183-y
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of rural and urban populations’ access to electricity: evidence from Pakistan

Abstract: Background: This study explores the electricity access to rural and urban populations and its impact on the economic growth in Pakistan. Methods: An autoregressive distributed lag (ARDL) bounds testing approach was applied, and a co-integration test was used to investigate the dynamic causality relationships between the study variables. By using this testing approach, this study filled the literature gap regarding the access of rural and urban population to electricity in Pakistan. Results: The tests shed ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
3
20
0
1
Order By: Relevance
“…Therefore, it can be said that "relation/ guanxi" is the key indicator of the stakeholders' satisfaction in any project setting, including REPs. The importance of stakeholders' satisfaction has also been observed in the literature of REPs [42,[52][53][54][55][56].…”
Section: Stakeholders' Influence In Constructing Successful Renewablementioning
confidence: 75%
“…Therefore, it can be said that "relation/ guanxi" is the key indicator of the stakeholders' satisfaction in any project setting, including REPs. The importance of stakeholders' satisfaction has also been observed in the literature of REPs [42,[52][53][54][55][56].…”
Section: Stakeholders' Influence In Constructing Successful Renewablementioning
confidence: 75%
“…All country panels, i.e., 15 EU countries, have lower elasticities of about 0.12 while the BRIC countries have higher elasticities of about 0.37. Weak substitutability relations between capital and energy determined for all groups were found, excluding the East EU and BRIC countries, demonstrating reverse relations [24]. W. Liu and Ayres [9,25] studied the link of economic performance with energy, and Lean and Smyth [26] with energy usage while Ahmad and Zhao [27] analyzed the link of economic performance to energy investment.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Electricity is a major source of energy and it is a prime policy issue for sustainable expansion. The accessibility of electricity helps meet household and domestic needs, stimulates export potentials of the country to create employment, reduces poverty, and, ultimately, improves socio-economic development [4,[30][31][32]. Electricity, therefore, plays a key role for the economic progression of a country, which brings much more assistance to all dynamic sectors of an economy [2,33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results revealed that usage of electricity leads to economic progression without feedback. Assessing the electricity access impact on economic progress for Pakistan, Reference [30] suggested the long-run positive association among variables. Furthermore, the growth-enhancing impact of electricity access has been confirmed for the urban population.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation